Utilization of Large-Sized Dolomite By-Product Particles and Losses of Cations from Acidic Soil. Issue 7 (12th April 2019) - Litvinovich, Andrey; Salaev, Ivan; Pavlova, Olga; Lavrishchev, Anton; Bure, Vladimir; Saljnikov, Elmira
ABSTRACT: To investigate the possibilities of utilization of dolomite large size fractions (dropouts) and their effect on plants a five-year experiment was set in 2015. A fertilization value of large fractions (5–7 and 7–10 mm) of dolomite in two doses was studied. The biomass yield of crops in dolomite dropout treatment was around 90% from the treatment using dolomite flour (control). Losses of bases from the soil treated with high doses of dropouts did not exceed the migration losses of the treatment with dolomite flour. Dynamics of dolomite flour dissolution in the soil was empirically modeled. The data prove that high doses of the large-sized dolomite fractions act similarly to standard dolomite flour and have more persistent effects on soil and plants.